Negotiating adult-child relationships in early childhood research - Albon, Deborah; Rosen, Rachel (London ; New York : Routledge, 2014)
'Negotiating Adult-Child Relationships in Early Childhood Research discusses the technical implementation of ethics in research with children through an exploration of the complicated and often'messy' situations faced in negotiating relationships in research with children. Despite growing acknowledgement of their centrality, relationships between adult researchers and very young participants have been neglected and under-theorised. In response, this book offers a comprehensive conceptualisation of adult-child research relationships through examination of questions, including: - How do power and inequity impact on adult-child research relationships? - What does it mean for relationships when researchers'intervene' in the field? - How do bodies matter in research relationships? - What does an emphasis on relationships with young children mean for the research process? Drawing upon data and case studies from the authors' own research to support the conceptual ideas under discussion, this insightful new book contributes to current debates about research with young children, offering a thorough exploration of the importance of relationships to the research process. Relevant for international audiences, this book is essential reading for early childhood students and educators, researchers, and lecturers with an interest in research with children, and will further the debate of early years research for undergraduate and postgraduate students alike'--
Includes bibliographical references (page 135-149) and index.
Keywords: Child development -- Research; Early childhood education -- Research; Children and adults